Guinbot-an Irrigators Service Association, Inc It's contribution to democratization and development. - Oriondo, Ben G. (Tacloban City Ben G. Oriondo, 2009)
In recent years, people have been interested in discussions about the changes of agricultural production in the world caused by global warming. From another viewpoint, I noticed that with current conditions, agricultural productions changes a great deal every year depending on various factors.
It was to this end that this paper wishes to convey information to the reading public about the immediate effect of the current agricultural conditions to the farming sector. Irrigation system in the Philippines basically has a great role in the development of agriculture as well as the increase in production.
The Guinbot-an Irrigators Service Association, Inc. (GISA), a service oriented group has been for many years a tool for the little farmers of San Julian municipality in terms of rendering service to the farmers. Eastern Samar, being farming dependent province, has encountered a lot of experiences which measures how the very foundation of the farming industry here can sustain the growing need for food and basic needs of human consumption.
The very basic aim of GISA is to render service to the farming sector in San Julian to increase the rate of production output in the agricultural sector. They are also equipped to sustain the irrigation system of the locality such that the rainfed dependent agricultural lands will still be productive even in times of the dry season.
Furthermore, the organization also is at the same time contributing to the development and democratization process characterized by the ways and means that its leaders impose on the members.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban.
Keywords: Social Science